2019
DOI: 10.1021/acs.langmuir.9b00686
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Sulfur Bond Cleavage During Adsorption of Octadecane Thiol to Copper in Ethanol

Abstract: The effect of the solvent on the formation of thiol self-assembled monolayers (SAMs) on oxide-covered, reactive metals is more involved than in the well-studied gold-thiol system. In this work, copper covered with a native oxide was modified with 1-octadecanethiol (ODT) in either tetrahydrofuran (THF) or ethanol. Infrared (IR) spectroscopy indicated the formation of crystalline chain packing of alkyl chains from both solvents. Surface coverage was approximately equal in both systems, with differences in tilt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…For instance, with regards to the tendency to produce atomic sulfur, which was confirmed for many metals, [84][85][86][87] but for Au(111). Moreover, slight changes in the organic backbone can induce the breaking of S-Au bond, 65 which highlights that also the chemical nature of the thiol matters.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, with regards to the tendency to produce atomic sulfur, which was confirmed for many metals, [84][85][86][87] but for Au(111). Moreover, slight changes in the organic backbone can induce the breaking of S-Au bond, 65 which highlights that also the chemical nature of the thiol matters.…”
Section: Discussionmentioning
confidence: 85%
“…Although comparisons of many two-dimensional molecular layers with them have been very useful, our study represents an example of how this approach is usually overestimated. It has been shown that the surface chemistry of thiols on many metals is different than that found on Au(111), for instance, with regard to the tendency to produce atomic sulfur, which was confirmed for many metals but for Au(111). Moreover, slight changes in the organic backbone can induce the breaking of the S–Au bond, which highlights that also the chemical nature of the thiol matters.…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to the idea that atomic sulfur comes from contamination, 20 it can be formed along with the SAM formation, or as a consequence of thiolate degradation. 18,21 Indeed, the C-S bond breaking of alkanethiolates has been reported for many metals with distinguishing catalytic properties as Pd 22 , Ni 21 , Cu 23 , and Pt 24 . On the other hand, long-chained alkanethiols only lead to alkanethiolate species when are chemisorbed on Au.…”
Section: Introductionmentioning
confidence: 99%
“…Looking closely to the SAMs’ degradation processes, there are several factors that influence the extension of a possible C–S bond breaking. Among them are the composition and structure of the substrate, the temperature, the solvent, and the chemical nature of the thiol. ,,, Then, to understand the SAMs’ degradation mechanism, many variables must be considered. More importantly, during and after C–S bond scission, the roles of the different chemical bonds in the whole thiol have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated the C-S bond scission of ODT on Cu substrates covered with a natural oxide layer. It was assumed that the solvation of ODT in ethanol weakens the C-S bond and therefore make the bond scission possible (Rechmann et al, 2019). Another work reported the C-S bond cleave on Ni(111), also known for its strong catalytic activity, at room temperature and therefore a considerable amount of atomic sulfur in their measurements (Blobner et al, 2015) is reported.…”
Section: Coverage and Layer Stoichiometrymentioning
confidence: 99%